The Effect of Special Exercises on Developing Strength Endurance and Kayaking Achievement Time (500m) individually for the Advanced Kayak Athletes - Abdul Latif, Moayad; Fadhel, Abdul Karim (Journal of Physical Education, 2020)
Using special exercises in sports training have great importance on developing achievement especially kayaking. The problem of the research lies in the achievement time of advance Iraqi national league kayak athletes in 500m due to special physical abilities weakness. The research aimed at identifying the effect of special exercises on developing strength and achievement of 500m kayaking. A training program was applied for two months with 3 training sessions per week. The subjects were (8) kayak athletes divided into two groups; experimental and controlling group. The researchers concluded that applying these special exercises have a positive effect on developing strength endurance and achievement development. Finally, they recommended using these exercises due to their great effect on developing physical abilities as well as athletic achievement.